Avaliação do potencial antiparasitário do extrato e frações de Terminalia catappa L. (Combretaceae) - ARAÚJO , Sandra Alves de (2023)
Leishmaniasis and Chagas disease are infectious-parasitic diseases caused by protozoa of the genera Leishmania and Trypanosoma, respectively. Natural products have been used as an alternative to the available drugs, responsible for high toxicity and development of resistance. Thus, the objective of this work is to evaluate the therapeutic potential of extracts and fractions obtained from Terminalia catappa on the parasites of the species L. amazonensis and T. cruzi. T. catappa leaves were collected, dried and powdered. The material was subjected to extraction with 70% ethanol by exhaustive percolation, and denominated hydroethanolic extract. Subsequently, the extract was diluted in H2O: MeOH (8:2) and subjected to extraction with hexane and ethyl acetate, obtaining the hexane fraction, the ethyl acetate fraction and the water-methanol fraction. In the experiments investigating the action of the extract and fractions of T. catappa on the T. cruzi parasite, the antioxidant activity, and ultrastructural alterations of the parasite after treatment were analyzed. The chemical characterization of the hydroethanolic extract and the ethyl acetate fraction carried out by mass spectrometry identified the presence of phenolic compounds. From all T. catappa extracts and fractions evaluated, the ethyl acetate and the aqueous fraction displayed the best antioxidant activity by 2,2-diphenyl-1-picryl-hydrazyl radical scavenging method (IC50 of 7.77 ± 1.61 and 5.26 ± 1.26 µg/mL respectively), and by ferric ion reducing method (687.61 ± 0.26 and 1009.32 ± 0.13 µM of Trolox equivalent/mg extract, respectively). The ethyl acetate fraction showed remarkable inhibitory activity against epimastigotes, trypomastigotes and intracellular amastigotes of T. cruzi with IC50 of 8.86 ± 1.13, 24.91 ± 1.15 and 85.01 ± 1.21 µg/mL, respectively, and showed no cytotoxicity for Vero cells (CC50 >1000 µg/mL). The treatment of epimastigotes with the ethyl acetate fraction induced severe ultrastructural changes such as cytoplasmic disruption, cellular disorganization, morphological variation, and loss of parasite integrity. It is concluded that the ethyl acetate fraction obtained from T. catappa leaves can be an effective alternative in the treatment and control of Chagas disease, being material for future investigations. Next, we evaluated the therapeutic potential of T. catappa extracts and fractions on L. amazonensis and investigated the immunomodulatory mechanisms responsible for this action. Anti-Leishmania assays showed that the ethyl acetate fraction exhibited activity against promastigotes (IC50 86.07 ± 1.09 µg/mL) and low cytotoxicity (CC50 517.70 ± 1.68 µg/mL). Additionally, the ethyl acetate fraction also inhibited the intracellular parasite (IC50 25.74 ± 1.08 µg/mL) with a selectivity index of 20.11. Treatment with T. catappa ethyl acetate fraction did not increase NO production, but increased TNF-α levels and decreased HO-1 and ferritin gene expression in macrophages stimulated with L. amazonensis. The total flavonoid and ellagic acid content for ethyl acetate fraction was 13.41 ± 1.86 mg QE/g and 79.25 mg/g, respectively. As for the action of the extracts on parasites of the genus Leishmania, we conclude that the ethyl acetate fraction has leishmanicidal activity and immunomodulatory mechanisms that contribute to its action. Finally, the ethyl acetate fraction of T. catappa demonstrated promising antitrypanosomatides and antioxidant properties for the treatment and control of Chagas disease and leishmaniasis, however, further studies are needed, especially in vivo models to reinforce our findings, and contribute to the elucidation of the mechanisms of action.